Perbandingan Efisiensi Cooling Tower Unit 2 PLTP Lahendong Sebelum dan Sesudah Overhaul - Fingki Astrika Kulo; Rolles Nixon Palilingan; Cyrke A. N. Bujung (Jurnal FisTa : Fisika dan Terapannya, 2023)
Geothermal Power Plant (PLTP) is a power plant that utilizes the heat generated by the bowels of the earth to produce electricity. efficiency is defined as the ratio between output and input in a process. Efficiency is one of the important equations in thermodynamics to determine how well the energy conversion or transfer process occurs. The research location of PLTP Lahendong unit 2 is located in Tondangow Village, South Tomohon District. This study aims to determine the comparison of the efficiency of cooling tower unit 2 before and after overhaul by processing data using the Ms. software application. Based on the results of the analysis, the efficiency value of the cooling tower of PLTP Lahendong Unit 2 before overhaul has an average value of 59% and the average value of cooling tower efficiency after overhaul is 63%. The magnitude of the efficiency comparison from the overhaul results in the average value of cooling tower efficiency increasing by 4%.